1994
DOI: 10.1111/j.1476-5381.1994.tb17067.x
|View full text |Cite
|
Sign up to set email alerts
|

Agonist‐induced desensitization of histamine Hi receptor‐mediated inositol phospholipid hydrolysis in human umbilical vein endothelial cells

Abstract: 1 The regulation of histamine-induced [3H]-inositol phosphate formation was studied in human cultured umbilical vein endothelial cells (HUVEC).2 Histamine (ECm 4.8 iLM) produced a 12.7 fold increase in [3H]-inositol phosphate formation over basal levels. Prior exposure to 0.1 mM histamine (2 h) produced a 78% reduction in the response to subsequent histamine (0.1 mM) challenge. The IC5o for this histamine-induced desensitization was 0.9 ;LM.3 The inositol phosphate response to histamine (0.1 mM) was inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Here we show, for the first time to our knowledge, that H 1 R gene expression is silenced early after the activation of CD4 + T cells. Modulation of H 1 R signaling, like that of other G protein-coupled receptors, is complex and includes receptor desensitization, internalization, and subsequent downregulation (41,42). Desensitization of H 1 R is induced by both agonist-specific (homologous) and agonist nonspecific (heterologous) pathways, mainly involving PKC-mediated phosphorylation of H 1 R (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Here we show, for the first time to our knowledge, that H 1 R gene expression is silenced early after the activation of CD4 + T cells. Modulation of H 1 R signaling, like that of other G protein-coupled receptors, is complex and includes receptor desensitization, internalization, and subsequent downregulation (41,42). Desensitization of H 1 R is induced by both agonist-specific (homologous) and agonist nonspecific (heterologous) pathways, mainly involving PKC-mediated phosphorylation of H 1 R (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…We assessed the degree of store emptying by examining the decline in the [Ca¥]é responses; maximal histamine responses were also measured before and after the sequence of pulses as another measure of store depletion. This protocol reduces the extent of any agonist receptor desensitization (unlikely since HUVEC histamine receptors desensitize over a matter of hours; McCreath et al 1994), but, more importantly, is likely to be a more efficient stimulus than continuous application by minimizing inactivation of release at the IP× receptor, as argued for caffeine at the ryanodine receptor . Also, where submaximal agonist stimulation selectively releases Ca¥ from a subpopulation of stores which is characterized by heightened sensitivity to Figure 3.…”
Section: Assessment Of the Degree Of Cell Synchronizationmentioning
confidence: 99%
“…Numerous studies have demonstrated that both endogenously expressed as well as heterologously expressed H1HRs exhibit hyporesponsiveness/desensitization when exposed to either PKC-activating agents or histamine (7,(13)(14)(15)(16)(17)(18)(19) and that agonist-specific desensitization can be associated with H1HR internalization or down-regulation (14,18). However, beyond a basic appreciation that the H1HR desensitizes and internalizes, little is known regarding the mechanisms by which these processes are mediated.…”
mentioning
confidence: 99%